Pengembangan Instrumen Penilaian Kemampuan Literasi-Numerasi pada Pembelajaran Sejarah di SMA Menggunakan Quizizz - Ginting, Aberlan; Aisiah, Aisiah (YASIN, 2025)
Assessment instruments for literacy–numeracy skills in history courses at SMA Negeri 1 Padang have not yet demonstrated sufficient innovation, necessitating the development of assessment tools that are more aligned with the demands of 21st-century competencies. This study aims to identify the development procedures and to examine the feasibility, practicality, and effectiveness of literacy–numeracy assessment instruments for history courses developed using Quizizz. This research is a research and development (R&D) study employing the ADDIE model, which includes the stages of analysis, design, development, and implementation. Data analysis techniques combined qualitative and quantitative approaches using a Likert scale. The results show that the developed literacy–numeracy assessment instruments for history courses fall into the “highly feasible” category, with average scores of 3.71 from material validators and 3.72 from evaluation validators. The practicality and effectiveness of the instruments are in the “very practical/effective” category, with average scores of 3.66 from history teachers and 3.67 from students. These findings conclude that the Quizizz-based literacy–numeracy assessment instruments for history courses are highly feasible, practical, and effective for measuring students’ literacy–numeracy skills in history learning.